What drives farmers’ behavior under climate change? Decoding risk awareness, perceived impacts, and adaptive capacity in northern Italy - Ricart, Sandra; Gandolfi, Claudio; Castelletti, Andrea (Heliyon, 2025)
Understanding climate change in a precise and timely manner may assist in gauging the occurrence and seriousness of its impacts, thereby boosting the adaptive capacity and responsiveness of farmers. This investigation looks into farmers' knowledge of climate change, their perception of risks and impacts, and the strategies they anticipate to tackle the challenges of adaptation. A well-structured online survey covering risk awareness, perception, and adaptation was used to randomly sample 460 respondents from 12 irrigation districts in northern Italy. Descriptive and multivariate statistics, including structural equation modeling, were employed to outline the profiles of farmers, explore the drivers shaping their behavior, and disentangle the magnitude and direction underpinning their adaptive capacity. Findings revealed that farmers recognize changes in climate and perceive its variability and effects, such as rising temperatures, extreme heat events, and irregular precipitation. Farmers blend adaptive measures, including climate services and insurance, with preventive mechanisms like reducing fertilizer use, rotating and diversifying crops, and introducing soil conservation techniques. However, they encounter obstacles such as poor government assistance, expensive investments and overlay intricate regulations. Regarding decision-making processes, the structural model demonstrated that 1) recognizing climate change can sensibly predict alterations in farmers’ behavior concerning climate impacts while 2) there is a lack of correlation between perceiving risks and implementing risk adaptation measures. Interestingly, factors such as farming experience, farm size, area under irrigation, and primary crop type significantly influence how risks are perceived and what measures are adopted. In light of these results, we offer guidance for upcoming research.